Propagation properties of partially coherent beams through turbulent media with coherent modes representation - Alavinejad, M.; Ashiri, F.; Ghafary, B. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2008)
The partially coherent beams propagating through turbulent atmosphere have been studied in the past using coherent mode representation. In this research, the propagation of any modes of Hermite–Gaussian beam in a turbulent atmosphere is investigated and analytical formula for the average intensity of these beams is derived. The power in bucket (PIB) for any modes is also examined. The number of modes which exist in a partially coherent beam with known degree of global coherence (ratio of correlation length and the waist width of the Gaussian–Schell model (GSM) beam) is determined and the PIB for partially coherent beams is investigated using coherent mode representation.
Optica Applicata, Vol. 38, 2008, nr 3, s. 549-558
Keywords: optyka; atmospheric turbulence; partially coherent beam; Hermite–Gaussian beam; power in bucket (PIB)